Application of new quintic polynomial B-spline approximation for numerical investigation of Kuramoto–Sivashinsky equation - Iqbal, Muhammad Kashif; Abbas, Muhammad; Nazir, Tahir; Ali, Nouman (Advances in difference equations, 2020)
A spline is a piecewise defined special function that is usually comprised of polynomials of a certain degree. These polynomials are supposed to generate a smooth curve by connecting at given data points. In this work, an application of fifth degree basis spline functions is presented for a numerical investigation of the Kuramoto–Sivashinsky equation. The finite forward difference formula is used for temporal integration, whereas the basis splines, together with a new approximation for fourth order spatial derivative, are brought into play for discretization in space direction. In order to corroborate the presented numerical algorithm, some test problems are considered and the computational results are compared with existing methods.